4-Thiofuranoid Glycal: Versatile Glycosyl Donor for the Selective Synthesis of β-anomer of 4'-thionucleoside and its Biological Activities - Haraguchi, Kazuhiro; Kumamoto, Hiroki; Tanaka, Hiromichi (Current Medicinal Chemistry, 2022)
The first highly diastereoselective synthesis of β-anomers of 4'-thionucleosides has been carried out by means of electrophilic glycosidation utilizing 3,5-O-(di-tertbutylsilylene) (DTBS)-4-thiofuranoid glycal as a glycosyl donor. The resulting glycosides were transformed into ribo-, 2'-deoxy-, and arabinofuranosyl nucleosides through a chemical transformation of the 2'-substituent. The additive Pummerer reaction of the glycal Soxide gave 1,2-di-O-acetyl-3,5-O-DTBS-4-thioribofuranose. The utility of the DTBSprotected 4-thioribofuranose has been demonstrated by the preparation of 4'-thio analogues of pyrimidine- and purine-4'-thioribonucleosides based on the Vorbrüggen glycosidation. Synthesis of 4'-thio-counterpart of C-nucleoside antibiotic tiazofurin has also been carried out. α-Face selective hydroboration of 1-C-aryl- or 1-C-heteroaryl-glycals obtained by cross-coupling of 1-tributylstannylglycal has furnished the respective β- anomer of 4'-thio-C-ribonucleosides, including 4'-thio analogue of nucleoside antibiotic pseudouridine and 9-deazaadenosine. On the basis of lithiation chemistry, 1-C- and 2-Ccarbon- carbon-substituted 3,5-O-(1,1,3,3-tetraisopropyldisiloxane-1,3- diyl) (TIPDS)- 4- thiofuranoid glycal were synthesized. These glycals enabled us to prepare 1'-C- and 2'-β- C-carbon-substituted 2'-deoxy-4'-thionucleosides, including thio-counterpart of antitumor nucleoside antibiotic angustmycin C. Furthermore, 1'-C-methyl-4'-thiothymidine emerged as a potent inhibitor of angiogenesis. In addition, 1'-C-methyl-4'-thiothymidine exhibited more potent inhibitory activity against thymidine kinase-deficient mutant of herpes virus than that of ganciclovir. Among the 4'-substituted 4'-thiothymidines, the 4'- C-cyano- and 4'-C-ethynyl derivatives inhibited replication of HIV variant resistant to 3TC (HIVM184V) as potently as HIV-1IIIB. In terms of the value of selectivity index (SI), 4'-C-cyano-4'-thiothymidine showed a 3-fold selective index (SI) than that of the corresponding thymidine derivative. Furthermore, 4'-C-ethynyl-2'-deoxy-4'-thioguanosine has a 20-fold better value (>18,200) than that of 2'-deoxyguanosine counterpart (933). Furthermore, 4'-azido-4'-thiothymidine emerged as a selective and potent anti-EBV agent. In terms of antineoplastic activity, 4'-azido- and 4'-C-fluoromethyl-2'-deoxy-4'-thiocytidine inhibited proliferation of human B-cell (CCRF-SB) and T-cell leukemia (Molt-4) cell lines, although the parent compound 2'-deoxy-4'-thiocytidine did not exhibit any cytotoxicity up to 100 μM. These facts concerning the biological activities suggested that replacement of the furanose oxygen with a sulfur atom is a promising approach for the development of less toxic antiviral and antineoplastic nucleoside antimetabolites. 4'- Thionucleoside also acts as a monomer for oligonucleotides (ONs) therapeutics, exhibiting superior biological properties. Therefore, this review provides a wide range of potential monomers for antisense ON and siRNA.
Keywords: antineoplastic activity